Penguatan Pendidikan Karakter Anak Usia Dini melalui Integrasi Kearifan Lokal - Rahma, Rahma; Lilianti, Lilianti; Rasid, Rasid (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2024)
This study aims to analyze the role of local wisdom in early childhood education in Kendari City, focusing on its implementation at early childhood education Fajriatul Hikmah Kota Kendari and early childhood education Tasawuta Wawotobi Unaaha. A qualitative descriptive research method was employed, with data collected through interviews, observations, and documentation. The findings indicate that teachers have a good understanding of local wisdom and its relevance in early childhood education, particularly in instilling cultural values such as mutual cooperation, obedience, and respect for nature. The integration of local wisdom is carried out through various learning activities, including storytelling of folk tales, the use of local languages, and traditional games. Additionally, parental and community involvement plays a crucial role in strengthening character education in children. However, the study also identified several challenges in implementing local wisdom, such as the lack of specialized training for teachers and limited time for incorporating cultural values into the curriculum. Therefore, policy support from the government, teacher training programs, and increased community involvement are necessary to optimize the implementation of local wisdom-based education.